Global readings : a Sri Lankan commentary on Paul's letter to the Galatians - DeSilva, David A. (David Arthur) (Eugene, Or. : Cascade Books, 2011)
Reading Scripture with a view to hearing its significance and challenge within its original, foreign context is the essence of exegesis and an anchor point for responsible hermeneutics. Reading Scripture alongside others from a significantly different social location also helps us see fresh aspects of the meaning of the text itself, as well as fresh angles on its challenge to Christian discipleship. This innovative commentary by respected New Testament scholar David deSilva is grounded in both approaches: a careful exegesis of Galatians as a basis for discerning the challenge of Scripture in any social location; and a reading of Galatians from the viewpoint of the challenges to living out its message among the churches in Sri Lanka, the result of extensive interaction with Christian leaders in Sri Lanka. Seeing the text afresh from within its ancient context and a different, modern social location will challenge readers in the West to consider once more Paul's message of transformation through the Spirit, with implications for Western Christians in their own context and in the larger global matrix of the Church universal.
Includes bibliographical references (p. 315-328) and indexes.
Keywords: Bible. -- Commentaries; Bible -- Hermeneutics; Sri Lanka -- Church history